Nocturnal asthma is affected by genetic interactions between RORA and NPSR1. Issue 6 (29th March 2019) - Gaertner, Vincent D.; Michel, Sven; Curtin, John A.; Pulkkinen, Ville; Acevedo, Nathalie; Söderhäll, Cilla; von Berg, Andrea; Bufe, Albrecht; Laub, Otto; Rietschel, Ernst; Heinzmann, Andrea; Simma, Burkhard; et al.
Abstract: Background: Neuropeptide S Receptor 1 ( NPSR1 ) and Retinoid Acid Receptor‐Related Orphan Receptor Alpha (RORA ) interact biologically, are both known candidate genes for asthma, and are involved in controlling circadian rhythm. Thus, we assessed (1) whether interactions between RORA and NPSR1 specifically affect the nocturnal asthma phenotype and (2) how this may differ from other asthma phenotypes. Methods: Interaction effects between 24 single‐nucleotide polymorphisms (SNPs) in RORA and 35 SNPs in NPSR1 on asthma and nocturnal asthma symptoms were determined in 1432 subjects (763 asthmatics [192 with nocturnal asthma symptoms]; 669 controls) from the Multicenter Asthma Genetic in Childhood/International Study of Asthma and Allergies in Childhood studies. The results were validated and extended in children from the Manchester Asthma and Allergy Study (N = 723) and the Children Allergy Milieu Stockholm and Epidemiological cohort (N = 1646). Results: RORA * NPSR1 interactions seemed to affect both asthma and nocturnal asthma. In stratified analyses, however, interactions mainly affected nocturnal asthma and less so asthma without nocturnal symptoms or asthma severity. Results were replicated in two independent cohorts and seemed to remain constant over time throughout youth. Conclusion: RORA * NPSR1 interactions appear to be involved in mechanisms specific for nocturnal asthma. In contrast to previous studies focusing on the role of beta 2 receptor polymorphisms in nocturnal asthma as a feature of asthma control or severity in general, our data suggest that changes in circadian rhythm control are associated with nighttime asthma symptoms.